25th Anniversary Article: Materials for High‐Performance Biodegradable Semiconductor Devices. (21st February 2014) - Hwang, Suk‐Won; Park, Gayoung; Cheng, Huanyu; Song, Jun‐Kyul; Kang, Seung‐Kyun; Yin, Lan; Kim, Jae‐Hwan; Omenetto, Fiorenzo G.; Huang, Yonggang; Lee, Kyung‐Mi; Rogers, John A.
<x xml:space="preserve">Abstract</x> We review recent progress in a class of silicon‐based electronics that is capable of complete, controlled dissolution when immersed in water or bio‐fluids. This type of technology, referred to in a broader sense as transient electronics, has potential applications in resorbable biomedical devices, eco‐friendly electronics, environmental sensors, secure hardware systems and others. New results reported here include studies of the kinetics of hydrolysis of nanomembranes of single crystalline silicon in bio‐fluids and aqueous solutions at various pH levels and temperatures. Evaluations of toxicity using live animal models and test coupons of transient electronic materials provide some evidence of their biocompatibility, thereby suggesting potential for use in bioresorbable electronic implants.